Turtle Flexion Reflex Motor Patterns Show Windup, Mediated Partly by L-type Calcium Channels - Johnson, Keith P.; Tran, Stephen M.; Siegrist, Emily A.; Paidimarri, Krishna B.; Elson, Matthew S.; Berkowitz, Ari (Frontiers in Neural Circuits, 2017)
Windup is a form of multisecond temporal summation in which identical stimuli, delivered seconds apart, trigger increasingly strong neuronal responses. L-type Ca2+ channels have been shown to play an important role in the production of windup of spinal cord neuronal responses, initially in studies of turtle spinal cord and later in studies of mammalian spinal cord. L-type Ca2+ channels have also been shown to contribute to windup of limb withdrawal reflex (flexion reflex) in rats, but flexion reflex windup has not previously been described in turtles and its cellular mechanisms have not been studied. We studied windup of flexion reflex motor patterns, evoked with weak mechanical and electrical stimulation of the dorsal hindlimb foot skin and assessed via a hip flexor nerve recording, in spinal cord-transected and immobilized turtles in vivo. We found that an L-type Ca2+ channel antagonist, nifedipine, applied at concentrations of 50 µM or 100 µM to the hindlimb enlargement spinal cord, significantly reduced windup of flexion reflex motor patterns, while lower concentrations of nifedipine had no such effect. Nifedipine similarly reduced the amplitude of an individual flexion reflex motor pattern evoked by a stronger mechanical stimulus, in a dose-dependent manner, suggesting that L-type Ca2+ channels contribute to each flexion reflex as well as to multisecond summation of flexion reflex responses in turtles. We also found that we could elicit flexion reflex windup consistently using a 4-g von Frey filament, which is not usually considered a nociceptive stimulus. Thus, it may be that windup can be evoked by a wide range of tactile stimuli and that L-type calcium channels contribute to multisecond temporal summation of diverse tactile stimuli across vertebrates.